Constrained nonlinear model predictive control for centrifugal compressor system surge including piping acoustic using closed coupled valve. Issue 1 (1st January 2017) - Imani, Hashem; Jahed-Motlagh, Mohammad Reza; Salahshoor, Karim; Ramazani, Amin; Moarefianpur, Ali
ABSTRACT: This paper deals with nonlinear model predictive control scheme for surge prevention in centrifugal compressors systems. To bring up the effects of the station's piping system on the compressor surge, nonlinear dynamic of compression system is considered that involve acoustic of compressor system. Close-coupled-valve (CCV), as a common control input in compression systems, is considered as an actuator and the mathematical model describing the flow dynamic of compression system is derived in the presence of CCV. For controlling the compressor system surge instability, nonlinear model predictive control (NMPC) is applied, whose allow to consider constraints on CCV actuator and states of system, significantly enlarge the operating region of the compressor and enhance the authority of the control system. Numerical simulations show that the proposed control system is able to meet the desired specifications in avoiding and active control of surge, in the presence of different types of disturbances occurring along the pipeline.